Physical properties of full and half Heusler alloys Co2CrAl and CoCrSb ,First principal study - Horimek, Cherifa; Gueddouh, Ahmed (Laghouat : Université Amar Telidji - Département des sciences de la matière, 2022)
The purpose being to propose materials that meet industrial needs . For this reason we are interested in this work to study a family of smart materials that are the Heusler alloys , this class of materials are shown to be able to overcome these challenges as potential candidates with interesting properties for spintronics. theoretical work is devoted to the study of Heusler alloys . We placed ourselves within the framework of the density functional theory using ab initio methods implemented in the Casteb package to study the magneto-electronic, chemical and mechanical properties . We studied the full Heusler as half metallic materials possessing high temperature , total Fermi polarization as well as a large magnetic moment . We have also developed a remarkable correction on energy gaps by the GGA method. Then , we proposed a new cubic phase of the half Heusler alloys characterized by a large magnetic moment as well as a high Curie temperature and which is relevant for future applications. We have proposed a new family of trinary Heusler alloys with remarkable properties at Fermi level called new spin gapless semiconductors . Finally , we studied Heusler alloys as candidates for superconductivity.